ASSESSMENT OF SELECTED ECOFORMS OF PISTACIA VERA L. FOR PRODUCTIVITY, DROUGHT TOLERANCE, DISEASE AND PEST RESISTANCE (FOOTHILL AREAS OF JIZZAKH REGION, REPUBLIC OF UZBEKISTAN) - Khudaynazarova Nargiza Khudoyarovna; Kholmatova Saidakhon Qurbonboy qizi; Eshankulov Bobomurod Inayatovich (Modern American Journals, 2025)
Pistachio (Pistacia vera L.) has been utilized by humans for various purposes since ancient times. In Central Asian countries, particularly in Uzbekistan, the pistachio industry is developing rapidly, mainly due to the growing global demand for pistachio nuts. Selection and propagation of high-yielding and high-quality pistachio genotypes are essential for sustainable production. Scientific research in this field contributes to the establishment of high-yielding and stress-tolerant pistachio plantations in the future.
Keywords: Mountain and foothill regions, irrigation, rainfed lands, forest reclamation, nut crop, pistachio, drought, heat tolerance, breeding.